A Study of Concrete Made with Fine and Coarse Aggregates Recycled from Fresh Concrete Waste. (26th August 2013) - Sérifou, Mamery; Sbartaï, Z. M.; Yotte, S.; Boffoué, M. O.; Emeruwa, E.; Bos, F.
Abstract : This paper deals with the possibility of using fresh concrete waste as recycled aggregates in concrete. An experimental program based on two variables (proportion of fine aggregates replacement and proportion of coarse aggregates replacement) was implemented. The proportions of replacement were 0%, 50%, and 100% by mass of aggregates. Several mechanical properties were tested as compressive and tensile strengths. The results show a good correlation between aggregates replacement percentage and concrete properties. Concerning mechanical properties, a gradual decrease in compressive, splitting, and flexural strengthn with the increase in recycled aggregate percentage is shown.